Phase evolution in plasma sprayed Nb2O5 coatings. Issue 10 (August 2021) - Caliari, Felipe R.; Garcia, Eugenio; Miranda, Felipe; Filho, Gilberto Petraconi; Sampath, Sanjay
Highlights: We report the in-situ formation of nonstoichiometry and metastable Nb2 O5-x phases within the range of 0.04 < x < 0.21. Metastable phases T, TT-Nb2 O5 are formed at the splat core and nonstoichiometry phases NbO2, Nb12 O29 at the splat boundaries. Ar/H2 thermal plasma-Nb2 O5 interaction is based on Nb2 O5 incongruent vaporization and rapid solidification. We report interesting thermal, electrical and thermomechanical properties of Nb2 O5-x deposits. Abstract: Nb2 O5 polymorphism and defect chemistry depend on the temperature, pressure, atmosphere composition and the initial crystallography. Plasma spray of Nb2 O5 is a pathway to form coatings with in-situ metastable and nonstoichiometric phases, however so far unexplored. This study aimed to understand the phase evolution of plasma sprayed Nb2 O5 coatings, and its effect on their morphology and properties. Phase evolution from H-Nb2 O5 in the feedstock, to T-Nb2 O5, TT-Nb2 O5, N-Nb2 O5, H-Nb2 O5, Nb12 O29 and NbO2 in the coatings depends on the plasma Ar/H2 ratio and its related enthalpy. The microstructure shows a layered distribution of nonstoichiometric phases at the splat boundaries and splat cores composed of T-Nb2 O5 or TT-Nb2 O5 . The presence and distribution of these phases are related to the thermomechanical and electrical properties. The mechanisms driving the formation of these coatings are based on the Nb2 O5 incongruent vaporization which promote retention of nonstoichiometric phases and the rapid solidification of metastable phases.